National Geographic Magazine [computer file] 1940s (vol. LXXVII, no. 1) Jan. 1940-April 1943, May 1943-August 1946, September 1946-December 1949 - Broderbund; National Geographic Interactive (Washington, CD National Geographic Society, 1888)
See the high-speed photograpjs of dazzling hummingbirds, captured on a film at 1/3000 of a second. Explore the ruins of Colorado's Mes Verda cliff dwellings. Relive the liberation of Paris in 1944, with soldiers parading down streets still echoing with the lockstep march of Nazi Storm trooper boots. And experience manay more captivating moments from the 1940s.
National Geography: The 1940s chronicles the tragedies and triumphs of this pivotal dacade.
On Danish, Denmark-Land of Tranquility; Whales, Giants of the Sea; Whals, Porpoises, and Dolphins; Southampton-Gateway to London; South Florida's Amazing Everglades
The complete National Geographic on CD-ROM was produced from archive of magazines collected in a central repository and is not representative of any single regional edition of National Geographic magazine.
Minimum requirements for Windows: Pentium 90MHz or faster, 24MB RAM, 70MB free hard-disk space, SVGA video card supporting 16-bit color, 16-bit sound card and speakers, 4x CD-ROM drive.
Minimum requirements for Macintosh: PowerPC or higher, System 7.5 or higher, 32MB RAM, 70MB free hard-disk space, 640x840 16-bit color monitor, 4x CD-ROM drive.
Keywords: Colorado's Masa Verde; Nazi